Clinical, Parasitological, and Serological Follow-Up of Dogs with Sarcoptic Mange Treated Orally with Lotilaner. (27th January 2021) - Moog, F.; Brun, J.; Bourdeau, P.; Cadiergues, M. C.
Abstract : Canine sarcoptic mange is a highly pruritic and contagious skin disease caused by the mite Sarcoptes scabiei var. canis . This case series describes the clinical, parasitological, and serological follow-up of a cohort of eight adult Saint Bernard dogs with confirmed sarcoptic mange, treated orally with lotilaner. Dogs were evaluated initially and after 14 days and 1, 2, 3, 4, 6, and 12 months for skin lesions, pruritus severity, presence of parasites, and Sarcoptes -IgG levels. A serological indoor allergy panel (IgE) was obtained for seven dogs at day 0 and repeated 12 months later in five dogs to assess potential cross-reactivity between S. scabiei and environmental allergens. Lotilaner was administered to each dog according to the manufacturer's instructions and was repeated after one and two months without any concurrent therapeutic measure or modification of the husbandry conditions. Pruritus ceased after two weeks. The cutaneous score was reduced by 47%, and skin scrapings were negative for all but three animals. All skin scrapings were negative after one month. Lesions were absent after two months. Serological levels decreased gradually, but more slowly than the skin lesions, and two dogs out of six remained positive in the absence of skin lesions or symptoms. All dogs initially tested positive for dust mites and/or storage mites. The IgE titres remained unchanged 12 months later in the five tested dogs. This case report demonstrates the efficacy of lotilaner on scabies in a cohort of infested dogs under natural conditions and the potential antigenic cross-reaction of S. scabiei with house dust and storage mites.